Temporal dynamics of the primary human T cell response to yellow fever virus 17D as it matures from an effector- to a memory-type response - Blom, Kim; Braun, Monika; Ivarsson, Martin A; Gonzalez, Veronica D; Falconer, Karolin; Moll, Markus; Ljunggren, Hans-Gustaf; Michaëlsson, Jakob; Sandberg, Johan K (The Journal of immunology (1950), 2013)
The live attenuated yellow fever virus (YFV) 17D vaccine provides a good model to study immune responses to an acute viral infection in humans. We studied the temporal dynamics, composition, and character of the primary human T cell response to YFV. The acute YFV-specific effector CD8 T cell response was broad and complex; it was composed of dominant responses that persisted into the memory population, as well as of transient subdominant responses that were not detected at the memory stage. Furthermore, HLA-A2- and HLA-B7-restricted YFV epitope-specific effector cells predominantly displayed a CD45RA(-)CCR7(-)PD-1(+)CD27(high) phenotype, which transitioned into a CD45RA(+)CCR7(-)PD-1(-)CD27(low) memory population phenotype. The functional profile of the YFV-specific CD8 T cell response changed in composition as it matured from an effector- to a memory-type response, and it tended to become less polyfunctional during the course of this transition. Interestingly, activation of CD4 T cells, as well as FOXP3(+) T regulatory cells, in response to YFV vaccination preceded the kinetics of the CD8 T cell response. The present results contribute to our understanding of how immunodominance patterns develop, as well as the phenotypic and functional characteristics of the primary human T cell response to a viral infection as it evolves and matures into memory.